(3fHPI eNJUQI ef Yjhf GdEUGHI aj efGbH GdTjN eMV HGHgs - (3ejdhO Hf GdeNJGQs ((3ehQjJGfjG s)
(3ChdgG (B:s
(3CeG HYO agPg LedI edJbWg ef Yjhf GdEUGHI ai efGbH GdTjN eMV HGHg dJdejPg GdYdGeI edjhO Hf GdeNJGQ hZjQgG LYdJgG cGdJQLeI dg hcJGHg GdejSQ fSHg QVi Gddg Yfg s
(3BNQgG (B:s
(3cKjQ ef GdCLdGA efge HGH CMeO HjHG GdYdhi abO hLOJ HNWg ai LRA GdfcGM ef HjGf GHf QTO s
(3HgG JBcd ai HYV ChQGbgGs
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI SjFI s
(3GdfSNI HgG JdhjK , JQeje s
Keywords: (3GdJGQjNs